Writing in English in Italy – from ‘compositions’ to ‘academic writing’ - Andrea Nava (EuroAmerican Journal of Applied Linguistics and Languages, 2023)
This article aims to investigate the evolution of L2 English writing instruction in the 20th century, focusing on the ‘pre-history’ of academic writing in Italy – when writing was mainly viewed as an ancillary activity, often added to grammar/translation language classes. To shed some light on the principles underlying L2 English ‘composition’ writing instruction, the article illustrates the findings of the analysis of a sample of English writing materials published in Italy between the 1940s and the 1990s. Against the background of a mostly stagnant institutional context, English writing pedagogy appears to have evolved in Italy throughout the 20th century as a result of wider social and cultural changes, as well as developments in applied linguistics. This evolution led to a reappraisal of the role of the learner writer, who was increasingly viewed as an active agent in the process of knowledge transformation.